Pedagogical Effectiveness of Arabic as a Foreign Language: A Comparative Perceptual Study of Teachers and Students in Islamic Senior High Schools - Abdurrahman, Abdurrahman; Syakhansyah, Zulfan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This research is motivated by the persistently low communicative proficiency in Arabic among students in formal Islamic senior high schools (madrasahs), which stems from a fundamental perceptual disconnect between educators and learners. The primary objective of this study is to evaluate pedagogical effectiveness through a comparative analysis of teacher and student perspectives on instructional strategies, digital resources, and psycholinguistic barriers. Employing a mixed-methods approach with an explanatory sequential design, data were collected via Likert-scale questionnaires administered to 4 teachers and 15 students at MA Raudlatul Ulum Putra, followed by in-depth interviews, classroom observations, and documentation of instructional tools. The results reveal a statistically significant Methodological Perceptual Gap (p 0.05) across all measured indicators. Teachers perceive traditional grammar-based methods as highly effective, while students report high levels of language anxiety (M = 4.60), cognitive burnout from grammatical overload (M = 4.40, t = 6.25), and a strong desire for more communicative, engaging instruction. Furthermore, although digital facilities are physically available (p 0.05), their utilization remains minimal, creating a provision-utilization gap (p 0.05). The findings demonstrate that teachers and students operate within fundamentally different perceptual frameworks: teachers prioritize curricular completion and grammatical accuracy, while students value practical communication, active engagement, and psychological safety. This study makes three significant contributions: (1) it empirically documents the existence and magnitude of perceptual gaps in madrasah Arabic instruction; (2) it extends the affective filter hypothesis to the Islamic schooling context; and (3) it provides a strategic framework for curriculum revitalization. The findings underscore the urgent need for a paradigm shift from theoretical-scholastic orientations toward communicative-affective approaches, with implications for teacher training, digital integration, and language environment design.